If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k * t + -1k = 3k Multiply k * t 3kt + -1k = 3k Reorder the terms: -1k + 3kt = 3k Solving -1k + 3kt = 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. -1k + -3k + 3kt = 3k + -3k Combine like terms: -1k + -3k = -4k -4k + 3kt = 3k + -3k Combine like terms: 3k + -3k = 0 -4k + 3kt = 0 Factor out the Greatest Common Factor (GCF), 'k'. k(-4 + 3t) = 0Subproblem 1
Set the factor 'k' equal to zero and attempt to solve: Simplifying k = 0 Solving k = 0 Move all terms containing k to the left, all other terms to the right. Simplifying k = 0Subproblem 2
Set the factor '(-4 + 3t)' equal to zero and attempt to solve: Simplifying -4 + 3t = 0 Solving -4 + 3t = 0 Move all terms containing k to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3t = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3t = 0 + 4 3t = 0 + 4 Combine like terms: 0 + 4 = 4 3t = 4 Add '-3t' to each side of the equation. 3t + -3t = 4 + -3t Combine like terms: 3t + -3t = 0 0 = 4 + -3t Simplifying 0 = 4 + -3t The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
k = {0}
| 3*7+4h=7 | | -2x^2+4=x^2+x-7 | | 2a+a-5=5 | | 0.5x+8=6 | | 4*4-2(-6)(-2)/(15+3*3)=x | | y-60=6(x-10) | | -(6y+5)-(-5y-7)=-6 | | z^2-1000x+60775=0 | | 2x+35/4=5 | | 4x+2*5-3x=1 | | 4*4=x | | 4*4=4*4 | | 13x-2y=-5 | | 9x+8=x | | 16=-2z | | 23t-8t^2=-3 | | 5-c/6=d-7c | | 3.5x+3.5x=-21 | | 15=-16t^2+30t+5 | | 25w^2-30w+9= | | -2(6x-8)+4=20 | | 4x+7x-15=0 | | q-3r=2r | | -6x+8y=-4 | | 4-8n=10 | | 4x+6x+4=0 | | 8+2r-4=9r+4-6r | | 5y+12=27 | | (x+7)2=144 | | 3s(6t)= | | -6=16t^2+46t | | 3/5+21/6=x |